INCREASING WORKPLACE SAFETY THROUGH THE IDENTIFICATION OF UNSAFE ACTIONS AND UNSAFE CONDITIONS IN THE NICKEL MINING SECTOR AT PT.X IN 2024 - Saptaputra, Syawal Kamiluddin; Amirudin, Agus (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Occupational safety and health (OSH) is a crucial aspect of workplace management. Unsafe actions (UA) and unsafe conditions (UC) can lead to accidents and injuries in the workplace. Objective : This study aims to reveal the dominant categories of UAs and UCs, along with the locations with the highest incident rates. Research Methods/ Implementation Methods : The research employs a mixed-method approach where data is collected through interviews, observations, and incident reports from various work locations. The analysis focuses on the frequency of UAs and UCs based on category and location during the period from January to June 2024. Results : The research findings indicate that the highest category of UA is poor housekeeping behavior, with 524 cases. The most frequently occurring UC is misplacement or improper storage, totaling 427 cases. The location with the most UAs was found in the main office, with 237 findings, while the location with the most UCs occurred at Comp 3 Denver, with 232 findings. Conclusion/Lesson Learned : To reduce unsafe actions (UA) and unsafe conditions (UC), it is essential for management to enhance awareness of good occupational safety and health practices. This can be achieved through routine training programs for all employees and the implementation of consistent supervision.